Triple-Mode Grid-Balancing Plants via Biomass Gasification and Reversible Solid-Oxide Cell Stack: Economic Feasibility Evaluation via Plant Capital-Cost Target - Zhang, Yumeng; Wang, Ningling; Li, Chengzhou; Pérez-Fortes, Mar; Duan, Liqiang; Van herle, Jan; Maréchal, François; Lin, Tzu-En; Wang, Ligang; Yang, Yongping (Frontiers in Energy Research, 2021)
Electricity production and consumption must be balanced for the electrical grid. However, the rapidly growing intermittent power sources are now challenging the supply-demand balance, leading to large flexibility needs for grid management. The plant integrating biomass gasification and reversible solid-oxide cell stacks can be potential means of flexibility, which could flexibly switch among power generation, power storage, and power neutral modes. This paper investigates the economic feasibility of such grid-balancing plants, i.e., plant capital expenditure (CAPEX) target, via a systematic overall decomposition-based methodology for real geographical zones and flexibility-need scenarios. The plant CAPEX target (€/ref-stack) is defined as the maximum affordable investment cost for each reference stack (active cell area 5,120 cm2). The results show that, for a 5-year payback time, 5-year stack lifetime, and 40 €/MWh grid balancing price, the plant concept with 10–100 MWth gasifier has high economic potential with target reaching 17,000 €/ref-stack; however, the plant concept with 100–1,000 MWth gasifier has a limited commercialization potential with the target reaching below 1,000 €/ref-stack due to high biomass supply costs. Considering the sale of chemical product, plant CAPEX target can reach up to 22,000 and 3,000–12,000 €/ref-stack for the plants with 10–100 and 100–1,000 MWth, respectively. The plant CAPEX target is decreased by increasing the total capacities of all plants deployed since more and more capacities will be put into power neutral mode (isolated from the electrical grid) via the coordination of multiple plants. The plant CAPEX target can be further increased by higher grid up/down-regulating price and longer payback years.